GOVERNMENT OF THE REPUBLIC OF UZBEKISTAN. THE OLIY MAJLIS OF THE REPUBLIC OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract explores the Government of the Republic of Uzbekistan, focusing specifically on the Oliy Majlis, the country's highest legislative body. Uzbekistan operates under a presidential system, with the Oliy Majlis serving as the national parliament comprising two chambers: the Legislative Chamber and the Senate. The roles and responsibilities of the Oliy Majlis include legislation, oversight of government activities, budget approval, and participation in international relations. The composition of the Oliy Majlis reflects a balance of regional and national interests, with members elected or appointed to represent constituencies across Uzbekistan. Over the years, the Oliy Majlis has evolved to embrace democratic principles and engage in legislative reforms aimed at promoting human rights and economic development. Challenges persist, including the need to strengthen democratic institutions and address socio-economic inequalities. Looking ahead, the Oliy Majlis is poised to play a central role in advancing Uzbekistan's development agenda and contributing to the country's integration into the global community.